Partial depolymerization of tamarind seed xyloglucan and its functionality toward enhancing the solubility of curcumin. (1st May 2023) - Lang, Weeranuch; Tagami, Takayoshi; Kang, Hye-Jin; Okuyama, Masayuki; Sakairi, Nobuo; Kimura, Atsuo
Abstract: Polysaccharides of tamarind seed, a byproduct of the tamarind pulp industry, displayed a potential solubility improvement of lipophilic bioactive molecules but their textural characteristics hinder the dietary formulation. In contrast, the commonly available xyloglucan oligosaccharides (XOSs) with degrees of polymerization (DPs) of 7, 8, and 9 were too short to maintain their ability. The binding capacity of the between sizes is unknown due to a lack of appropriate preparation. We prepared xyloglucan megalosaccharides (XMSs) by partial depolymerization, where term megalosaccharide (MS) defines the middle chain-length saccharide between DPs 10 and 100. Digestion with fungal cellulase enabled reproducible active XMSs. Further identification of pure XMS segments indicated that XMS-B has an average DP of 17.2 (Gal3 Glc8 Xyl6 ) with a branched dimer of XOS 8 and 9 and was free of side-chain arabinose, the residue influencing high viscosity. Curcumin, a bioactive pigment, has poor bioavailability because of its water insolubility. XMSs with average DPs of 15.4–24.3 have similarly sufficient capacities to solubilize curcumin. The solubility of curcumin was improved 180-fold by the addition of 50 %, w/v, XMSs, which yielded a clear yellow liquid. Our findings indicated that XMSs were a promising added-value agent in foods and pharmaceuticals for the oral intake of curcumin. Graphical abstract: Unlabelled Image